Use of carbon-13 and carbon-14 to measure the effects of carbon dioxide and nitrogen fertilization on carbon dynamics in ponderosa pine - Paul, Eldor A., author; Ball, J. T., author; Johnson, D. W., author; Cheng, W., author; Haile-Mariam, Shawel, author; Soil Science Society of America, publisher (Colorado State University. Libraries, 2000)
Soil C sequestration in predicted, future elevated CO2 environments will be important to atmospheric CO2 levels, soil tilth, and fertility. An elevated CO2 study with ponderosa pines (Pinus ponderosa Laws) grown in chambers produced above ground vegetation with a δ13C of −44‰ and roots with −42‰. This together with carbon dating made it possible to follow soil C dynamics. Fifty percent of the California upland soil C, resistant to acid hydrolysis, was designated as the resistant fraction. Carbon dating showed the mean residence times of this fraction to be 400 to 1500 yr greater than the total soil C for the horizons sampled. Young ponderosa pines grown in CO2 chambers produced negligible leaf litter. There were 32% more roots in the presence of either added N or double CO2 but 77% more in the presence of both. Root-derived soil C was equivalent to 10% of the root C after the 6-yr growth period. Analysis of laboratory CO2 evolution during extended incubation showed the active soil C pool represented 1 to 2% of the soil C with a field-equivalent mean residence time (MRT) of 24 to 53 d. The slow pool represented 46 to 52% of the C with MRT of 24 to 67 yr depending on treatment and soil depth. Analysis of the 13CO2 label during incubation from the elevated CO2 treatments, showed the root-derived 13C of the active fraction to have residence times similar to those of the total soil non labeled C at ≈35 d. Root-derived C of the slow pool at 10 yr MRT turned over three to four time as fast as the general soil C. The 13C of the light fraction (LF), showed it to be most closely associated with the active pool. The particulate organic matter (POM) was part of the slow pool as determined with incubation.
Keywords: atmospheric N; elevated CO2; N fertilization treatments; CO2